Seroprevalence of anti-Leptospira spp. antibodies in dogs in Bahia, Brazil - Lavinsky, Manuella Oliveira; Abou Said, Roueda; Reuss Strenzel, Gil Marcelo; Langoni, Hélio [UNESP] (Elsevier B.V., 2012)
The aim of this study was to determine the prevalence of anti-Leptospira spp. antibodies in dogs living in the urban area of the city of Ilheus, Bahia, Brazil using the microscopic agglutination test (MAT) to investigate 24 serovars. A semi-structured questionnaire was administered to dog owners to collect data about demography, husbandry and environmental factors. The prevalence of anti-Leptospira spp. antibodies in the population of 282 dogs was 7.1% (95% confidence interval: 4.4-10.7%). Serovar Copenhageni was the most prevalent, followed by serovars Bratislava, Canicola and Gryppotyphosa. No risk factor was detected with regard to demography (age, gender and breed), husbandry (Leptospira vaccinations, food and water exposure through their environment, hunting habits, contact with other animals and contact with rats) and environmental factors (sewage network, garbage collection, history of flooding, river proximity and wastelands). Despite the low prevalence found in this study, the seroprevalence of Leptospira spp. in healthy dogs in Ilheus indicates the presence of this agent in the environment, which may be a source of human infection. Knowledge of the serovars present in this environment is important for understanding the epidemiology of leptospirosis and establishing public health policies aimed at its control. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Leptospirosis; Canine; Zoonosis